Volcano Vol.2 - Magloff, Lisa (London Dorling Kindersley, 2006)
For years, tourists have trekked across cracked rock at Hawaii's Kilauea volcano to witness the awe-inspiring sight of creeping lava and its devastating effects on the landscape. In 2010, Eyjafjallajökull erupted in Iceland, stranding travellers as a cloud of ash covered western and northern Europe, causing the largest disruption of air travel since the Second World War. And just a few months later, Mount Merapi
Include Color Illustration, Index and Glossary
Keywords: Volcanic eruptions -- California--Los Angeles